PATTERN OF ACUTE POISONING ADMISSIONS IN THE MEDICAL INTENSIVE CARE UNIT OF A TERTIARY CARE HOSPITAL (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Poisonings comprise an important health issue and leading cause of hospital admission and mortalities in developing countries. This study aims to evaluate the incidence, drug utilization pattern and cost of intensive care associated with poisonings in a tertiary care center. Participants comprised of acute poisoning admissions to the Medical Intensive Care unit of A J Hospital & Research Center, Mangalore during 6 months period. Data regarding pattern of poisoning, basic demographics and drug utilisation were collected by retrospective review of patient records Prevalence of poisoning was 35.49 cases per 1,000 hospitalizations. Majority of poisoning cases were observed in the age group between 25-44 years (85%). Intentional self-poisoning to Organophosphorous compounds and drug over dosage by sedatives were the most common patterns of poisoning observed. Parameters related to drug utilization exhibited slight variations with the agent consumed. Mortality rate was less probably due to timely medical management. Prevailing treatment protocols require updating on proper guidelines for better management of poisoning. There is need for stringent pesticide regulation laws and counselling and training programs to reduce incidence of poisonings.